Kinematics characteristics of key point of interest during tennis serve among tennis players: a systematic review and meta-analysis - Jacquier-Bret, J.; Gorce, P. (Frontiers in Sports and Active Living, 2024)
The objective of this systematic review and meta-analysis was to provide an overview of kinematic parameters associated with key points of interest in the tennis serve. The research was conducted according to the PRISMA guideline without date restriction. Google scholar, Science Direct, PubMed/Medline, Mendeley, and Science.gov databases were scanned to find relevant studies. Only English peer-review original article focused on joint body angles at trophy position, racket low point and ball impact were retained. The review, quality appraisal, and data extraction from selected studies were performed independently by two reviewers. A meta-analysis was carried out on the most studied joint parameters. Among the 2,844 records identified, 27 articles were included. The wide variety of methods used required data homogenization for comparison purposes. Trunk inclination (25.0 ± 7.1°) and front knee flexion (64.5 ± 9.7°) were the most studied parameters for trophy position. Shoulder lateral rotation (130.1 ± 26.5°) was systematically evaluated for racket low point. At ball impact, shoulder elevation (110.7 ± 16.9°) and elbow flexion (30.1 ± 15.9°) were the most considered joint angles. The systematic review revealed that many kinematic parameters were not quantified at the various key points of interest. Knowledge of the kinematics is essential for understanding the gesture, implementing training methods, and improving the performance.